APPLICATION OF CONTRAST LIMITED ADAPTIVE HISTOGRAM EQUALIZATION (CLAHE) AND GAUSSIAN FILTER METHODS FOR IMPROVEMENT OF IMAGE QUALITY ON CLOSED CIRCUIT TELEVISION (CCTV) - Nurul Hadi Muliani Hariadi Saputra; Armansyah; Mhd Furqan (INFOKUM, 2022)
The results of video recordings from CCTV cameras depend on the quality of the CCTV facilities themselves, some can capture results from dark rooms or vice versa. If the room has a lot of light, then the CCTV footage looks good, if the room lacks light, the CCTV camera results only see objects that have light, so there are some sides of the object that look dark and the results of the objects recorded are not optimal. So to minimize dark CCTV catches, It is essential to have a system that can boost the performance of CCTV, especially on CCTV screenshots. Methods that can be used to improve the quality of CCTV images are CLAHE and Gaussian Filter methods. CCTV pictures captured in low light may have their contrast stabilized using the CLAHE technique, and noise can be removed using the Gaussian Filter method. Based on the CLAHE test, it was able to increase the contrast of CCTV with clip limit histogram, and the Gaussian Filter succeeded in eliminating CCTV image noise while maintaining the quality of CCTV images from CLAHE, this is based on the MSE value which is close to 0 (zero). Keywords: Enhancement, CCTV, Imagery, CLAHE, Gaussian Filter.